Karst, Mining and Conflict — A Historical Perspective of the Consequences of Mining on the Far West Rand - Stoch, E.J.; Winde, F.; Erasmus, E. (Mine Closure 2008: Proceedings of the Third International Seminar on Mine Closure, 2008)
This paper, which covers some personal experiences, provides a timely reminder that the loss of crucial information, collectively referred to as ‘institutional memory’, in respect of the political and administrative arrangements with high significance on the Far West Rand, can have serious consequences for mine closure. The content brings together three parties, of whom two represent opposite sides of a water ‘war’ — a farmer and a consultant — with a moderating and impartial third party from abroad. Since the advent of mining on the Far West Rand during the 1930s, several parallel but interrelated events have unfolded, impacting upon each other and left a legacy that changed the socio-economic tenure not only of the area, but also in settings as remote as parliament and global stock exchanges. Each major event led to a host of studies that have made the Far West Rand one of the best studied mining areas in the world. In practice the ad hoc studies produced many unrelated data segments that are hosted in a number of insecure archives. Furthermore along the timeline, there is a range of undertakings and liability partnerships that include government pre- set closure conditions, some of which have conveniently been forgotten. The main author, a 50+ year ‘participant’ in the events on the Far West Rand, recounts his experience with Dolomitic groundwater and selected parallel developments that impacted on the area in a non-technical overview that illustrates the wide scope and volume of work done over more than 100 years in the Wonderfontein catchment. Some of the lessons that can be learned from this unique experience, using the pre-mining groundwater studies as a baseline and taking into account the advent of mining, resultant dewatering and the unforeseen scale of ground movement, may assist those whose task it will be to plan for mine closure. Closure of the mines of the Far West Rand is a given. Rehabilitation is thus not an option that can avoid the consequences of a reversal of the dewatering policy when the pumps stop. The possibility of reactivating the ground movement and the associated threat of pollution cannot be discounted if the process is not managed. It can, therefore, be argued that the experience which is on record could repeat itself in reverse. The history of the area presents a strong argument, in the case of the Far West Rand, to take cognizance of the potential pitfalls and why what is left of the institutional memory should be secured for posterity.